Forage-Fed Insects as Food and Feed Source: Opportunities and Constraints of Edible Insects in the Tropics - Espitia Buitrago, Paula Andrea; Hernández, Luis Miguel; Burkart, Stefan; Palmer, Neil; Cardoso Arango, Juan Andrés (Frontiers in Sustainable Food Systems, 2021)
Farmed insects can provide an alternative protein source for humans, livestock, and fish, while supporting adaptation to climate change, generating income for smallholder farmers, and reducing the negative impacts of conventional food production, especially in the tropics. However, the quantity, nutritional quality and safety of insects greatly relies on their feed intake. Tropical forages (grasses and legumes) can provide a valuable and yet untapped source of feed for several farmed insect species. In this perspective paper, we provide a viewpoint of how tropical forages can support edible insect production. We also highlight the potential of tropical forage-based diets over those using organic agricultural or urban by-product substrates, due to their versatility, low cost, and lower risk of microbial and chemical hazards. The main bottlenecks relate to dependence on the small number of farmed insect species, and in public policy and market frameworks regarding the use of edible insects as food, feed and in industrial processes. This perspective will serve interested stakeholders in identifying urgent issues at the research, ethical, marketing and policy levels that can prevent the emergence of new, insect-based value chains and business models, and the nutritional, economic and environmental benefits they promise.